2019
DOI: 10.33751/jf.v8i1.1168
|View full text |Cite
|
Sign up to set email alerts
|

RED GINGER (Zingiber officinale var. rubrum): ITS CHEMICAL CONSTITUENTS, PHARMACOLOGICAL ACTIVITIES AND SAFETY

Abstract: Ginger (Zingiber officinale) which belongs to the Zingiberaceae family, was first cultivated in Asia (Indonesia and Malaysia). This plant is one of the most commonly used herbal supplements taken by many patients to treat various conditions. Z.officinale has three varieties based on its size, colors of rhizome and chemical constituents i.e. .Z. officinale var. officinale (big white ginger or giant ginger, badak or gajah), Z. officinale var. amarum (small white ginger, emprit), and Z. officinale var. rubrum (sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 3 publications
0
8
0
8
Order By: Relevance
“…Red ginger juice has a strong aroma so that the aroma of different gelling agents does not affect the aroma of the jelly sticks [7]. The aroma score ranges from 4.1 to 4.6, which means it has a slightly ginger aroma.…”
Section: Organoleptic Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Red ginger juice has a strong aroma so that the aroma of different gelling agents does not affect the aroma of the jelly sticks [7]. The aroma score ranges from 4.1 to 4.6, which means it has a slightly ginger aroma.…”
Section: Organoleptic Testmentioning
confidence: 99%
“…These compounds are phenolic compounds such as gingerol, shogaol, and zingerone [6]. The types of ginger that grow in Indonesia can be distinguished based on the size, color of the rhizome and its content, namely big white ginger (gajah), small white ginger (emprit), and red ginger [7].…”
Section: Introductionmentioning
confidence: 99%
“…LD50 is defined as the dose of a substance that will result in at least 50% mortality when administered to a given number of animals. While some studies reported Zingiber officinale LD50 to be less than 2000 mg/kg (Anosike et al, 2009;Supu et al, 2018;Benny et al, 2021), others reported a higher LD50 of 4525 mg/kg (Abdulrazaq et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Many scientific studies worldwide have proven the efficacy of red ginger in a wide array of diseases—metabolic, neurological, cardiovascular, infectious, and cancer. Despite red ginger being relatively safe [ 94 , 95 ], consuming large amounts of ginger can cause hypoglycemia and spontaneous miscarriage [ 96 , 97 ]. However, there are no reports of clinical studies om red ginger.…”
Section: Discussionmentioning
confidence: 99%